Dampak Implementasi Kebijakan Taksi Mina Bahari Pada Produktivitas Nelayan Tradisional - Sukarman Kamuli (Universitas Riau, 2012)
The implementation of Taksi Mina Bahari (TMB) policy is the action program inGorontalo Province in the field of fisheries and marine Gorontalo as an effort to improve theproductivity of traditional fishermen fishing. The purpose of this study were: 1) analyzing theimpact of the implementation of TMB policies on the productivity of traditional fishermen fishing,and 2) studying the approach model used in order to achieve the successful implementation ofpolicies TMB. Who were respondents in the study sample as many as 70 people of 187 populationby using the estimated rule of thumb. Data were collected through questionnaires and analyzedwith a statistical model of SEM. Based on the results of the statistical test SEM models, it showsthat the implementers of policy factor on the success of policy implementation TMB, while factorof community figures support is regarded as very weak factor to determine the success of policyimplementation TMB. Research findings revealed that the best and the appropriate approachmodel forthe conditions of fishing communities is a dialogic approach model.